Parents' perceptions of core outcomes in neonatal research in two Nigerian neonatal units - Ian Sinha; Melissa Gladstone; Janneke van de Wijgert; Kevin Mortimer; Sarah Kathryn Read; Aisha Jibril; Olukemi Tongo; Abimbole Akindolire; Isa Abdulkadir; Helen Nabwera; Stephen Allen; Olusegun Akinyinka; et al. (BMJ Publishing Group, 2020)
Background There is a scarcity of information regarding the most important outcomes for research in neonatal units in low-resource settings. Identification of important outcomes by different stakeholder groups would inform the development of a core outcome set (COS) for use in neonatal research.Objective To determine the perceptions and opinions of parents of newborn babies regarding what outcomes were most important to them in order to contribute towards development of a COS for neonatal research in sub-Saharan Africa.Methods Semistructured interviews were undertaken with parents, mostly mothers, of babies admitted to one neonatal unit in North central and one in Southwest Nigeria. Participants were purposively sampled to include parents of babies with common neonatal problems such as prematurity.Results We conducted 31 interviews. The most frequently raised outcomes were breast feeding, good health outcomes for their baby, education, growth and financial cost. Parents placed more emphasis on quality of life and functional status than health complications.Conclusions The opinions of parents need to be considered in developing a COS for neonatal research in low-resource settings. Further research should assess the opinions of families in other low-resource settings and also engage a broader range of stakeholders.